2018
DOI: 10.4103/joc.joc_134_17
|View full text |Cite
|
Sign up to set email alerts
|

Role of rapid on-site evaluation in CT-guided fine needle aspiration cytology of lung nodules

Abstract: Objective:To prospectively investigate the value of rapid on-site evaluation (ROSE) in transthoracic fine needle aspiration cytology (FNAC) of patients with pulmonary nodules. Computed tomography (CT)-guided FNA is commonly employed for the diagnosis of lung lesions and the most common reason for not being able to provide a diagnosis in FNA is inadequacy of samples.Materials and Methods:This was a prospective study conducted in the departments of pathology and radiology of our cancer centre. This study had app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 10 publications
2
25
0
1
Order By: Relevance
“…Unfortunately, few studies have focused on the diagnostic accuracy of ROSE by comparing it with histopathology. Consistent with a study by Anila et al, 14 we found that ROSE had excellent efficacy in determining adequacy of specimens. In three cases, ROSE resulted in a false negative result of inadequacy and these cases were diagnosed as adenocarcinoma, primary tracheal leiomyoma, and atypical cells by histopathology.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Unfortunately, few studies have focused on the diagnostic accuracy of ROSE by comparing it with histopathology. Consistent with a study by Anila et al, 14 we found that ROSE had excellent efficacy in determining adequacy of specimens. In three cases, ROSE resulted in a false negative result of inadequacy and these cases were diagnosed as adenocarcinoma, primary tracheal leiomyoma, and atypical cells by histopathology.…”
Section: Discussionsupporting
confidence: 92%
“…This patient was finally diagnosed with adenocarcinoma after surgery. A similar situation was previously reported, 14 and there was speculation that a difficult biopsy or intolerance of the patient caused few specimens to be obtained. Additionally, fragmentation of specimens into pieces and diagnostic material with a different distribution might have caused this situation.…”
Section: Discussionsupporting
confidence: 78%
“…While obtaining specimens, we reduced the times of punctures as much as possible. Ten patients underwent CT-guided lung biopsy, as ROSE was performed during the puncture process to increase the positive rate of specimens (17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…On-site cytology evaluation has shown to improve a diagnostic accuracy and reduce needle passes in image-guided transthoracic needle aspiration. 29,30 It is not clear whether additional diagnostic gain could be obtained when a core biopsy needle is used. However, in the case of FNA, the combination with ROSE provides a comparable diagnostic accuracy to that of a core needle biopsy for malignant lesions.…”
Section: Rapid On-site Evaluation (Rose)mentioning
confidence: 99%
“…On-site cytology evaluation has shown to improve a diagnostic accuracy and reduce needle passes in image-guided transthoracic needle aspiration [ 27 , 28 ]. It is not clear whether additional diagnostic gain could be obtained when a core biopsy needle is used.…”
Section: How To Maximize Diagnostic Accuracymentioning
confidence: 99%